Curriculum of EFL Teacher Education and Indonesian Qualification Framework: A Blip of the Future Direction - Susilo, Susilo (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Indonesian Qualification Framework (IQF) is a description of qualification levels for all Indonesian learning outcomes or certificate statements in Indonesian schooling from year 9 to higher education. The IQF holds a legal endorsement in the form of Presidential Decree no. 8/2012. This IQF will specify equivalencies between Indonesian and foreign qualifications, thus improving Indonesia’s international competitiveness and making the country more open to global trade. As a consequence, the structures of curriculum in all Indonesian educations should base on this document. Defined as the expanding circle countries in Kachru’s concentric circles, Indonesia needs English language teacher education with appropriate structures of curriculum relevant to the global world and 21st century learning. This article intends to describe the IQF, the 21st Century learning, and the upcoming structure of the EL Teacher education Curriculum in Indonesia. More specifically, this article aims at analyzing: 1) how Indonesian Teachers should develop their curriculum according to the IQF descriptors; 2) how macro-social factors in SLA such as global and national status of L2, boundaries and identities, or institutional forces and constraints should be considered in the development of the curriculum structures of English language teacher education; and 3) how the 21st century trends should be blended in the curriculum.